2015
DOI: 10.1037/sgd0000141
|View full text |Cite
|
Sign up to set email alerts
|

Psychological help-seeking attitudes and intentions of lesbian, gay, and bisexual individuals: The role of sexual minority identity and perceived counselor sexual prejudice.

Abstract: In the current study, the psychological help-seeking attitudes and intentions of 140 lesbian, gay, and bisexual (LGB) individuals were examined in relation to their LGB identity and perceived sexual prejudice of mental health counselors. Relying on the theory of planned behavior (Ajzen, 1991), the looking glass self (Cooley, 1902(Cooley, /1964, and the threat-to-self-esteem model (Nadler & Fisher, 1986), we hypothesized that perceived counselor sexual prejudice mediated the relationship between an individual's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 62 publications
2
22
1
1
Order By: Relevance
“…For our study, the scores for Stigma Tolerance and Expertness were combined to reflect a composite measure of attitudes toward seeking psychological help and Intent remained a standalone subscale (cf. Spengler & Ægisdóttir, 2015). We changed the wording of the original scale from seeking help from a “psychologist” to a “counselor” to be more generalizable to the field of mental health counseling.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For our study, the scores for Stigma Tolerance and Expertness were combined to reflect a composite measure of attitudes toward seeking psychological help and Intent remained a standalone subscale (cf. Spengler & Ægisdóttir, 2015). We changed the wording of the original scale from seeking help from a “psychologist” to a “counselor” to be more generalizable to the field of mental health counseling.…”
Section: Methodsmentioning
confidence: 99%
“…Kite and Deaux (1986) established initial construct validity through significant correlations with a scale measuring attitudes toward traditional gender roles (Smith, Ferree, & Miller, 1975). Following Spengler and Ægisdóttir (2015), we reworded items to reflect how participants believed a counselor would answer them. For example, the item “I won’t associate with known homosexuals if I can help it” was reworded to “A counselor won’t associate with individuals known to be lesbian or gay if they can help it.” Kite and Deaux reported strong internal consistency (Cronbach’s alpha = .93); Spengler and Ægisdóttir reported similar reliability in their modified version (Cronbach’s alpha = .90), and we observed a Cronbach’s alpha of .97.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its publication, numerous findings have supported the validity of the LGBIS subscales. Among the most important are arguably the findings that pointed to critically important links between LGBIS subscales and health-related variables, such as mental health (Mereish & Poteat, 2015; Morandini et al, 2015; Puckett et al, 2015), gay men and lesbian women’s intentions to seek a psychotherapist’s help (Spengler & Ægisdóttir, 2015), physical health risk behavior (Harper et al, 2015), or physical health (Denton et al, 2014). For instance, Denton et al (2014) deployed the three LGBIS subscales Internalized Homonegativity, Acceptance Concerns, and Concealment Motivation and found that Internalized Homonegativity and Acceptance Concerns were weakly to moderately associated with LGB participants’ self-reported physical symptoms such as sleep problems or headaches ( r = .15 and r = .22, respectively; p s < .01).…”
Section: The Lesbian Gay and Bisexual Identity Scale (Lgbis)mentioning
confidence: 99%
“…Within the behavioral health domain, factors of sexual orientation identity significantly relate to psychological help-seeking attitudes in LGB individuals (Spengler & Ægisdóttir, 2015). Identity affirmation, which includes positive attitudes regarding one's sexual orientation as well perceiving support from the community, positively relates to increased help-seeking attitudes.…”
mentioning
confidence: 99%